Interaction of Perfluorooctanoic Acid with terrestrial plants: Uptake, transfer and phytotoxicity aspects. Issue 1 (31st December 2022) - Li, Hongyuan; Wang, Yujing; Du, Wenchao; He, Huan; Yang, Shaogui
ABSTRACT: Soil contamination with perfluorooctanoic acid (PFOA) is a global concern. PFOA in soil can enter plants, affect plant growth and threaten food safety. Therefore, understanding the plant utilization and phytotoxicity of PFOA is conducive to assessing the environmental risk of soil contaminated with PFOA. This review analyzed recent studies about the uptake and effects of PFOA on terrestrial plants from the aspects of absorption, transport, distribution, phytotoxicity, and the underlying mechanism. Based on current research, PFOA was predominantly taken by plant roots and showed adverse effects on plants by affecting the antioxidant system and metabolic process. Research in field or higher terrestrial plants is still very scarce. Given the importance of exploring the potential remediation methods for PFOA, more research with comprehensive consideration of soil and environmental factors should be carried out to tell its specific mechanisms of plant utilization and toxicity action.